Analytical Study of Thalangi Ennai: A Pain Relieving Siddha Medicated Oil - Vinotha, S.; Sri Ranjani, S.; Ira, T. (University of Colombo, 2012)
Thalangai ennai is one of the Siddha medicated oil mentioned in the siddha Pharmacopeia and it is prepared at siddha Drag Unit in Jaffna and supplied to all Government District Ayurvedic Hospital, Rural Ayurvedic Hospitals and Central Ayurvedic Dispensaries in Jaffna District. Thalangai ennai is indicated for various vata disorders such as rheumatic pain, bone degeneration and impaired movement of limbs. It is a compound medicine and its ingredients are juice of the thalangai (Pandanus tectorius), sesame oil, milk, water, rock salt and seventeen different herbal powdered materials.
Keywords: Thalangai ennai; Siddha medicine; Pain relieving; Medicated oil